Transformational Leadership and Organizational Culture on Employee Engagement With Work Satisfaction as an Intervening Variable - Pamara, Florensya; Bayudhirgantara , Emanuel Michael (Journal Research of Social Science, Economics, and Management, 2022)
The level of involvement that an employee has in a company can change at different times. When it comes to the reality of organizational expansion, it is very important for organizations to have engagement that can become a real possibility both physically and non-physically. The purpose of this study was to determine the relationship between transformational leadership, organizational culture, and employee engagement, using job satisfaction as an intermediary metric. This study uses a quantitative methodology and utilizes the Smart-PLS application to collect data. The data collection technique consisted of a questionnaire submitted by 67 Mimika Land Office workers using Google Form. Transformational leadership has a sizeable impact on job satisfaction, but not on employee engagement, according to the study. Organizational culture, however, has a major impact on employee happiness and employee engagement. As a final point, if job satisfaction has a major impact on employee engagement, and if organizational culture has a significant impact on employee engagement, then transformational leadership is able to moderate the effect of employee engagement on job satisfaction.